Teaching about Food, Sex and Gender in the Classroom - Wilk, Richard (Kvinder, Køn & Forskning, 2017)
Teaching about Food, Sex and Gender in the Classroom: In this essay Richard Wilk shares his experience with teaching a course on food, sexuality and gender and the challenges it proved to provide during the semester: not only was finding literature and putting the syllabus together demanding tasks, there was also a series of rather uncomfortable, affective moments in the class during the semester. Wilk presents perspectives on teaching the theme of food, sexuality and gender and highlights the importance of current discussions about gender and sexuality in contemporary food studies.